Deficits and debt in industrialized democracies - Ide, Eisaku; Park, Gene 1971- (Routledge research in comparative politics v 63, 2015)
Featuring the work of an international interdisciplinary team of scholars, this volume explains patterns of fiscal performance (persistent patterns of budget deficits and government debt) from the 1970s to the present across seven countries - France, Italy, Germany, Japan, South Korea, Sweden, and the United States. Employing a comparative case study approach, seldom employed in studies of fiscal performance, contributions illuminate the complex causal factors often overlooked by quantitative studies and advances our theoretical understanding of fiscal performance